METACHRONOUS COLORECTAL LIVER METASTASES HAS BETTER PROGNOSIS - IS IT TRUE? - Claudemiro QUIREZE JUNIOR; Andressa Machado Santana BRASIL; Lúcio Kenny MORAIS; Edmond Raymond Le CAMPION; Eliseu José Fleury TAVEIRA; Matheus Castrillon RASSI (Arquivos de Gastroenterologia)
ABSTRACT BACKGROUND: Liver metastases from colorectal cancer are an important public health problem due to the increasing incidence of colorectal cancer worldwide. Synchronous colorectal liver metastasis has been associated with worse survival, but this prognosis is controversial. OBJECTIVE: The objective of this study was to evaluate the recurrence-free survival and overall survival between groups of patients with metachronous and synchronous colorectal hepatic metastasis. METHODS: This was a retrospective analysis of medical records of patients with colorectal liver metastases seen from 2013 to 2016, divided into a metachronous and a synchronous group. The Cox regression model and the Kaplan-Meier method with log-rank test were used to compare survival between groups. RESULTS: The mean recurrence-free survival was 9.75 months and 50% at 1 year in the metachronous group and 19.73 months and 63.3% at 1 year in the synchronous group. The mean overall survival was 20.00 months and 6.2% at 3 years in the metachronous group and 30.39 months and 31.6% at 3 years in the synchronous group. Patients with metachronous hepatic metastasis presented worse overall survival in multivariate analysis. The use of biological drugs combined with chemotherapy was related to the best overall survival prognosis. CONCLUSION: Metachronous colorectal hepatic metastasis was associated with a worse prognosis for overall survival. There was no difference in recurrence-free survival between metachronous and synchronous metastases.